CREATIVITY AND COLLABORATION THROUGH THE PROJECT BASED LEARNING MODEL IN SCIENCE LEARNING - Fisyahrina , Amalia; Wulandari, Ria (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The purpose of this study was to determine the improvement and influence of creativity an collaboration through Project Based Learning models in science learning. This type of research is quantitative pre-experiment with aone group pretest-posttest design tested on the experimental class and 2 replication classes. The type of test used measure creativity uses a description test sheet while collaboration uses a collaboration observation sheet. The results showed that the increase in creativity with an average N-Gain value in the medium category. The collaboration skill scores of the three classes were obtained in the good and excellent categories. The result of the manova test on creativity and collaboration skills influenced creativity and collaboration through the Project Based Learning model so it can be concluded that the learning process using the Project Based Learning model can improve and influence creativity and collaboration in science learning